CFD modeling of hydrodynamics, combustion and NOx emission in a tangentially fired pulverized-coal boiler at low load operating conditions - Jian Chang; Xin Wang; Zhijian Zhou; Honggang Chen; Yuguang Niu (Advanced Powder Technology, 2021)
With deep peak-load regulations, utility boilers are frequently operated under variable/low load conditions. However, their hydrodynamics, combustion and NOx emission characteristics are uncertain and relevant theoretical guidance are lacking. For this purpose, a comprehensive CFD model including flow, coal combustion and NOx formation is established for a 630 MW tangentially fired pulverized-coal boiler, aiming at solving the problem of decreasing combustion stability and increasing NOx emission in low-load operation. Based on the grid independence and model validation, the flow field, temperature profile, species concentration profile and NOx emission are predicted, and the influences of angle/arrangement of burners are further evaluated. Simulation results indicate that under low-load conditions, residual airflow rotation still persists at the top of boiler regardless of how to adjust the angle/arrangement of burners. With tilting the burner angle upward, flame is more concentrated, combustion becomes more stable, and heat flux rises in the upper zone; the burner arrangement of ABDE gives more uniform temperature distribution in the combustion zone. CO species shows higher content in the combustion zone; the 0° tilt angle gives maximum CO content, followed by the 15° angle, and finally the −15° angle; compared to the ACDE and ABCE arrangement, the ABDE arrangement mode gives much lower CO contents. Burner tilt angle of −15° benefits for lower NOx emission (183 mg/m3) but goes against stable combustion; the burner arrangement mode of ABDE is optimal for the present boiler, which ensures both stable combustion and lower NOx emission (209 mg/m3).
Keywords: cfd; combustion; Low load; NOx emission; Pulverized-coal boiler; Tangentially fired